Unusual Assembly and Conversion of Graphene Quantum Dots into Crystalline Graphite Nanocapsules. Issue 12 (8th May 2017) - Gao, Jian; Xu, Chenyu; Hu, Yue; Zhao, Fei; Shao, Changxiang; Zhao, Yang; Chen, Shilv; Qu, Liangti
Abstract: The development of a facile strategy for conversion of graphene quantum dots (GQDs) into crystalline graphite is of great practical significance and still remains challenging. Herein, rationally assembled crystalline‐intercrossed graphite nanocapsules (CI‐GNCs) have been realized by a one‐step electrochemically induced strategy with the assistance of a soft template, in which the GQDs act as the initial building blocks. The as‐prepared CI‐GNCs exhibit highly crystalline graphitic nanostructures. Moreover, they possess promising electrocatalytic activity for the oxygen reaction reduction (ORR) in alkaline medium. This simple fabrication technology presents a great advance for synthesizing CI‐GNCs composite catalysts, which have potential as new metal‐free catalysts for efficient ORR applications. Abstract : Graphite nanocapsules with high crystallinity are formed from 2–5 nm graphene quantum dots via an unusual electrochemical strategy. The as‐prepared nanocapsules are highly crystalline and possess promising electrocatalytic activity for the oxygen reaction reduction (ORR) in an alkaline medium, which makes them promising new metal‐free electrocatalysts.